Validation of an Eastern Armenian breast cancer health belief survey. - Haley Tupper; Razmik Ghukasyan; Armine Bayburtyan; Arin Balalian; Arsine Kolanjian; Marine Hovhanissyan; Shant Shekherdimian (Public Library of Science (PLoS), 2023)
With the fourth highest breast cancer mortality rate in the world, breast cancer prevention and early detection is a priority for Armenia. The Ministry of Health recently initiated efforts to expand access to breast cancer screening. However, little is known about the population's understanding and perception of breast cancer screening programs. This cross-sectional telephone-based study sought to develop and validate an Eastern Armenian language version of the Champion's Health Belief Model Scale (CHBMS) for future use. The English-language CHBMS survey was first rigorously translated by two Armenian nationals and evaluated for face validity. Telephone surveys were then administered to randomly-selected women of approximately screening age (35-65 years) with no prior history of breast cancer living in Armenia's capital between 2019-2020 (n = 103). The translated survey's psychometric properties were evaluated, examining (1) content equivalence, (2) test-retest reliability and (3) internal consistency. Content equivalence and test-retest reliability of the Armenian CHBMS were characterized using correlational analysis with Pearson's coefficient ranging from 0.76-0.97 (p<0.001) and 0.72-0.97 (p<0.001), respectively, for all five CHBMS domains. The translated survey's internal consistency was comparable to the original English-language CHBMS with a Cronbach's alpha greater than 0.7 for all five domains (0.75-0.94 (p<0.001). The translated Eastern Armenian version of CHBMS is a valid, internally-consistent, and reliable research tool that is ready for imminent use among screening-age women to investigate breast cancer perceptions and beliefs as the Armenian government seeks to expand screening access.